The Landscape of Social Protection Programmes in Nepal - Maharjan, Nabin; Acharya, Saroj; Thapa, Sandhya (Journal of Social Protection, 2021)
Stimulating social protection programmes have a greater impact on the lives of people. More than 80 social protection programmes are being implemented by the Government of Nepal. The development partners, bilateral and multilateral agencies have been assisting the government for a long time however, the gap is realised in the programme integration and lack of inter-ministerial cooperation to set the results. 12 federal ministries are regulating social protection programmes through provincial and local governments. Some programmes have similar nature and might have certain duplication in beneficiaries, thus leaving the eligible ones excluded from the support. Based on the information gathered from year-wise reports of federal ministries, government line ministries, and various development partners, set the priority areas to enhance sufficient programme strategies for better social protection coverage. This article highlights the federal social protection schemes and programmes that are scattered, the status of beneficiaries, social accountability, and identifies the challenges faced by beneficiaries and the justification of the requirement on an integrated social protection framework.